Relationship between Talent Management Practices and Employee Performance - NATSAGDORJ, Solongo; Altanchimeg; SODOV, Ariunaa; Bayilatu, Bayilatu (Nurture, 2026)
This study examines the impact of talent management practices on employee performance in the Mongolian banking sector, addressing the growing need for evidence-based human resource strategies in emerging economies. The study focuses on four core components of talent management: Talent attraction, talent retention, training and development, and career planning. Data were collected through a structured questionnaire from 343 employees of the State Bank of Mongolia and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Measurement model assessment confirmed adequate reliability, convergent validity, and discriminant validity of the constructs. The structural model results indicate that all four talent management components have a positive and statistically significant effect on employee performance (p < 0.01). Among these, talent attraction, retention, training and development, and career planning each contribute meaningfully to improving employee performance outcomes. The findings suggest that effective implementation of comprehensive talent management practices enhances employee performance within the banking context. This study contributes to the talent management literature by providing empirical evidence from a developing country context and extending the application of established theoretical frameworks, including the Resource-Based View, AMO model, and Social Exchange Theory, to the Mongolian banking sector.